The Influence of Compassionate Leadership and Psychological Empowerment on Job Satisfaction Mediated by Psychological Well-Being - Virgil, Rama; Utami, Hamidah Nayati; Riza, Muhammad Faisal (Wacana Journal of Social and Humanity Studies, 2025)
This study aims to identify and explain the influence of compassionate leadership and psychological empowerment on job satisfaction, mediated by psychological well-being. This research assists PT. Bimaruna Jaya in East Jakarta focuses on decision-making and policy development to address and manage factors that impact employee job satisfaction. A proportionate random sampling technique was employed, resulting in a sample of 69 respondents, using a quantitative approach. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the aid of SmartPLS 4 software. The results indicate that compassionate leadership and psychological empowerment have a positive and significant impact on job satisfaction, which is mediated by psychological well-being. It is recommended for PT. Bimaruna Jaya East Jakarta will implement open and transparent employee recognition to help employees feel a sense of well-being and empowerment. Keywords: Compassionate Leadership, Job Satisfaction, Psychological Empowerment, Psychological Well-Being